Immunofluorescence microscopy for the rapid diagnosis of melioidosis. - Walsh, A; Smith, MD; Wuthiekanun, V; Suputtamongkol, Y; Desakorn, V; Chaowagul, W; White, N (1994)
A direct immunofluorescent antibody test (DIF) was developed for the rapid diagnosis of melioidosis, a potentially fatal infection caused by Pseudomonas pseudomallei. In a clinical evaluation of 369 sputum, pus, or urine specimens from 272 patients with suspected melioidosis, the DIF had a sensitivity of 73% and a specificity of 99% compared with culture. Using this DIF, a confident diagnosis of melioidosis can now be made within two hours of admission to hospital, compared with the delay of two to four days required for culture results. Consequent early institution of specific antimicrobial therapy may help to save lives.